2017
DOI: 10.1371/journal.pone.0170344
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Co-Treatment Attenuates the Effects of HIV Protease Inhibitors on Rat Body Weight and Enhances Cardiac Mitochondrial Respiration

Abstract: Since the early 1990s human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) emerged as a global health pandemic, with sub-Saharan Africa the hardest hit. While the successful roll-out of antiretroviral (ARV) therapy provided significant relief to HIV-positive individuals, such treatment can also elicit damaging side-effects. Here especially HIV protease inhibitors (PIs) are implicated in the onset of cardio-metabolic complications such as type-2 diabetes and coronary heart disease. As th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…RE co-treatment was also reported to attenuate the effects of several other drugs. For example, RE can attenuate the effects of Human immunodeficiency virus (HIV) protease inhibitors [146], and it can interact with 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA reductase) inhibitors [147], anti-arrhythmic agents [148], calcium channel agonists [149], antihistamines [150], and immunosuppressants [151].…”
Section: Resveratrol Interacts With and Attenuates The Action Of Othementioning
confidence: 99%
“…RE co-treatment was also reported to attenuate the effects of several other drugs. For example, RE can attenuate the effects of Human immunodeficiency virus (HIV) protease inhibitors [146], and it can interact with 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA reductase) inhibitors [147], anti-arrhythmic agents [148], calcium channel agonists [149], antihistamines [150], and immunosuppressants [151].…”
Section: Resveratrol Interacts With and Attenuates The Action Of Othementioning
confidence: 99%
“…Then, a RESV cotreatment, provided that suitable plasma concentrations are reached (Calvo-Castro et al, 2018), may help to overcome the side effects. Of note, RESV was reported to attenuate the effects of PIs on rat body weight while improving the cardiac parameters (Symington, Mapanga, Norton, & Essop, 2017). A putative role of UCP1 may account in part for these observations although no information regarding its expression is provided.…”
Section: Resveratrol Partially Reversed Lpv's Effect On Ucp1 Expressionmentioning
confidence: 99%
“…Nevertheless, nor RSV or RSVO was able to prevent this alteration in our experimental model. A pilot study demonstrated that a 4-month protocol of treatment with RSV prevented the body weight loss elicited by anti-HIV protease inhibitors in rats [49]. It is tempting to suggest that a long-term of treatment with RSVO might prevent CFA-related body weight reduction.…”
Section: Discussionmentioning
confidence: 99%